Eco-Education: Integrating Nature into Counselor Education. Issue 1 (2nd January 2020) - Duffy, Jason Thomas; Springer, Sarah; Delaney, Megan; Luke, Melissa
ABSTRACT: This consensual qualitative research study investigated the experiences of 10 counselors-in-training after exposure to nature-based interventions during a semester-long human development class. Interview data revealed four central domains: interpersonal impact, intrapersonal impact, whole-group impact, and feedback on nature-based activities. These findings highlight the benefits of eco-education for counselor development.